Penerapan Sistem Kontrol Berbasis IoT Pada Pompa Air Pertanian Di Desa Batur - Sri Kusumastuti; Sindung Hadwi Widi Sasono; Raditya Artha Rochmanto; Vinda Setya Kartika; Achmad Fahrul Aji (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Batur Village, Batur Sub-district, Banjarnegara District, faces challenges in managing water for agricultural purposes. The current manual irrigation system is time- and labor-intensive and increases the risk of pump damage. To overcome this, an Internet of Things (IoT)-based pump control system is implemented to improve efficiency and productivity. The system automatically activates the water suction pump based on the water level in the reservoir and sets the irrigation schedule. The implementation process includes site survey, system design, installation, training, and evaluation. The system allows farmers to monitor and control irrigation through a smartphone-based application. The implementation results show that the system can reduce manual work, minimize the risk of pump damage, and ensure optimal water availability. In addition, this technology supports more efficient water management, increases agricultural yields, and provides a positive economic impact for farmers.